GAMBARAN ADAPTASI ANAK YATIM PIATU PENDERITA TUNARUNGU DIPANTI ASUHAN FEBE TONDANO - Dessy N. Andries; Melkian Naharia; Marssel M. Sengkey (PSIKOPEDIA, 2022)
In general, a child who lives with biological parents will find it easier to adapt to their environment because children get more guidance from their parents. But not all children are lucky to have a complete family as experienced by children in orphanages. Every human being created by God has advantages and disadvantages. Children with hearing impairment need environmental adaptations in order to adapt well. A good adaptation for a deaf child who is in the Febe Tondano Orphanage does not happen instantly, but through the process of the people around him. Purpose In this study to get an overview and analysis of adaptation to deaf orphans at the Febe Tondano orphanage. researchers used qualitative methods. The approach used in this research is a case study, the number of subjects studied is 1 person. data collection techniques used are observation and interviews. The results of the study showed that the factors that influenced the adaptation process were physical condition, personality, learning process, environment, religion and culture, most of the subjects were able to adjust. Even though the subjects were still assisted by friends and caregivers who were in the orphanage environment.